DAMPAK PENGGUNAAN MEDIA PHET DAN ALAT PERAGA PRAKTIKUM TERHADAP PEMAHAMAN KONSEP GETARAN HARMONIK SEDERHANA PADA SISWA SMA - Nisbayanti, Nisbayanti; Novianti, Aisyah; Rahmadani, Nurul Astuti (Lembaga Penelitian Mahasiswa Penalaran UNM, 2020)
At present the average score of achievement of Indonesian students in science is ranked 62 out of 69 countries evaluated. Indonesia's ranking and average score is not much different from the previous PISA survey in 2012 which was also in the low level of material mastery group. Therefore, laboratories in every school that have teaching aids in them are very necessary to conduct practicum in increasing students' understanding of a concept in science. The purpose of this study is to make a comparison between teaching aids and PhET media on the understanding of student concepts. This type of research is a quasi-experimental with non-equivalent group design. The study was conducted at SMAN 1 Gowa in class X MIA 3 using PhET media and class X MIA 1 using media props based on purposive sampling technique. The results showed an increase in understanding of concepts using PhET. The results of the study also showed that there was an increase in understanding of the concept by using teaching aids.